Dirāsah ‘an al-ghazw al-thaqāfiy wa al-hazīmah al-nafsiyyah - Saifullah Kamalie (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2016)
Indonesia is the largest Muslim populations in the world. According to the 2011 census, there was about eighty eight percentage (nearly two hundred and five million Muslims) of the total population of this country. Does this largest number of Muslims demonstrate their Islamic identity in Indonesia? This country has attracted imperialist countries to colonize, invade and plunder its resources. Although Indonesia reached its independence on 7 August 1945, this country still witnesses other types of colonization in terms of information and communication technology, which have led particularly its Muslims to neglect their ‘Islamic identity’ and generally its people to neglect their predecessors’ efforts to obtain the freedom of this country.DOI: 10.15408/insaniyat.v1i1.4389